2017
DOI: 10.1055/s-0042-116823
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Hyperoxia Affect Serum Angiogenic Regulators in T2DM Men during Cycling

Abstract: Exercise-induced transient increases in pro-angiogenic regulators can promote angiogenesis.This pilot study aims to analyze the potential of exercise to positively affect angiogenic regulators in patients with type 2 diabetes mellitus (T2DM), who often exhibit abnormal angiogenesis, under different environmental conditions. 9 overweight/obese men with uncomplicated T2DM (8 took anti-diabetic drugs) performed submaximal cycling for 40 min in normoxia (≈21 vol%O), hypoxia (≈14 vol%O) and during alternating hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 36 publications
1
27
1
2
Order By: Relevance
“…Recent studies of T2D patients have shown that combining physical exercise with exposure to hypoxia (Hx) (FiO₂ = 14.7 %), a powerful glucose transport stimulator [20][21][22], improves moderate-term (up to 48 h) glycaemic control and insulin sensitivity [20,23]. Moreover, exercise and hypoxia have been shown to increase the activity of erythrocytes' NO synthase (ery-NOS) and to reduce the expression of proinflammatory cytokine -tumor necrosis factor alpha (TNF-α) [24].…”
Section: Effects Of Hypoxia During Continuous and Intermittent Exercimentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of T2D patients have shown that combining physical exercise with exposure to hypoxia (Hx) (FiO₂ = 14.7 %), a powerful glucose transport stimulator [20][21][22], improves moderate-term (up to 48 h) glycaemic control and insulin sensitivity [20,23]. Moreover, exercise and hypoxia have been shown to increase the activity of erythrocytes' NO synthase (ery-NOS) and to reduce the expression of proinflammatory cytokine -tumor necrosis factor alpha (TNF-α) [24].…”
Section: Effects Of Hypoxia During Continuous and Intermittent Exercimentioning
confidence: 99%
“…The study by Zebrowska et al [29] showed that shorttime hypoxia (FiO₂ = 15.1 %) combined with graded exercise allowed more effective glycaemia control in T1D patients when compared with the exercise in normoxia. Submaximal exercise with hypoxia (FiO₂ = 14.0 %) may induce up-regulation of serum pro-angiogenic regulators compared to normoxia in T2D [23].…”
Section: Effects Of Hypoxia During Continuous and Intermittent Exercimentioning
confidence: 99%
“…Brinkmann et al . indicated that alternating hypoxia/hyperoxia may induce a more reliable pro-angiogenic regulators up-regulation compared with normoxia 11 . Furthermore, several studies have been reported that high oxygen concentrations can modulate mRNA expression of several genes and related protein secretion including hypoxia inducible factor (HIF)-1α (a master oxygen sensitive transcriptional regulator), vascular endothelial growth factor-A (VEGFA), and interleukin (IL)-8 15 , 19 - 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been found that O 2 supplementation as a treatment has some beneficial effects for several diseases, such as chronic cardiopulmonary disease, diabetes and ischemia wounds 8 - 11 . Although increased O 2 supply has already been demonstrated that it has beneficial effects including improve action on tissue oxygenation via increased the amount of dissolved O 2 in blood, promote angiogenesis and improve wound healing 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation